The Bacillus genus applied to the biological control of plant diseases (Research, Society and Development, 2021)
To meet the growing world demand for food free of chemical residues, many microorganisms have been used as biocontrol agents for important phytopathogens and pests in important commercial crops. The genus Bacillus is widely used for this purpose, so the objective of this article was to concentrate the main updates on the genus, considering biological, taxonomic, genetic aspects and the applicability and potential of this group of prokaryotes in biological management actions of other organisms. The research demonstrates great versatility of the Bacillus genus with the capacity to occupy different niches, among them: soil, forage, water, and food; in addition to having many characteristics that define a good biological control agent, they are also widely applied in the management of phytomatomatoids. With technological advances, through studies of molecular biology, it became evident the possibility of using the genus Bacillus in biological management, thus being the focus of important scientific research.